Nuclear Terrorism as a possible threat to Africa - Henwood, Roland David (University of Pretoria, 2018)
This study investigates Nuclear Terrorism as a possible threat to Africa by means of a systematic literature review. The danger posed by terrorist groups in acquiring and using nuclear, chemical or biological weapons is more pronounced today than in the past, as terrorist groups have shown more interest in upgrading to more sophisticated tactics in their conduct of terror activity and adapt to more modern and advanced ways and means. Africa has a significant role in preventing the possible threat of nuclear terrorism as it continues to be vulnerable to the unlawful trade and trafficking of radioactive uranium because of its deficient control and regulatory systems which are often prone to malfunction and corruption, such as the existing weak borders that are not effectively controlled in several parts of the continent; the inadequate safety of the operating uranium mining and production sites in Africa; and the prevailing weak and corrupt governing institutions. The study’s emphasis is on the full implementation of the United Nations Security Council (UNSC) Resolution 1540 (2004) as a central counter-terrorism and non-proliferation instrument in Africa and as a mutually reinforcing and inter-related legal mechanism which complements and reinforces the Nuclear Non-Proliferation Treaty (NPT). The research also revises the role of regional treaties such as the African Nuclear-Weapon-Free Zone Treaty (Treaty of Pelindaba), which supports UNSC Resolution 1540 in realising Africa’s efforts in reducing the risks of nuclear proliferation, such as nuclear terrorism. The study remarks on the viewpoint and attitudes towards these initiatives and the role of the African Union (AU), and examines the progress made so far in executing the obligations of the UNSC Resolution 1540 by African member states. While there is growing international agreement that the threat of nuclear terrorism is real, understanding how the threat and perceptions of it have evolved clarifies the challenges faced by governments and policymakers today. In the identification of the research theme and motivation of the research study, the paper proposes two policy questions that guide and direct the research moving forward, namely: (1) how real is the risk to Africa? and (2) what policy measures would be most effective in reducing the risk? Simply put, what is the appropriate and relevant response by African states to the issue of the possibility of the acquisition and use of nuclear weapons by terrorist organisations?